Stomorija – Miri (Kaštel Novi), an example of spatial relations within settlements in late Antiquity and the Middle Ages (Archaeologia Adriatica, 2022)
In the paper the author substantiates the presence of two different concepts of spatial articulation of agrarian settlements in Kaštela in Late Antiquity and the Middle Ages. They were both formed in the complexes of villae rusticae that had been organized in Late Antiquity on the foundations of the early Roman villas. They differ from the latter in the size of accompanying estate, and in physical terms in much better preservation of architectural remains, since these villas continued to be used in the Middle Ages. In each of them a Christian sacral structure was built in the 6th century at the latest in the process of Christianization of pagus in the Salonitan ager. In the first, somewhat more common version of spatial articulation within a late antique estate (villa rustica), a Christian place of worship was erected in the residential and economic hub of the villa (St Martha – Stombrate, SS Cosmas and Damian – Dolac in Kaštel Gomilica). While the first version is common across the province of Dalmatia, the one in the case of Miri – Stomorija is most likely an exception caused by the local terrain features. In both cases these late antique complexes grew into medieval estates (curtes, predia), and then into medieval villages.